2019
DOI: 10.25046/aj040652
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Qualitative Study of the Influence of Hospital Logistics Factors on Quality of Care and Patient Satisfaction at Public Hospitals in Morocco

Abstract: The purpose of this qualitative research was to explore the influence of hospital logistics on quality of care and patient satisfaction. Hospital logistics was assessed by considering five factors in the patient pathway, namely: physical accessibility of care, waiting time, consultation time, administrative procedures and hospital hotel services. Semi-structured interviews were conducted, following an interview guide, with two categories of participants: patients and healthcare professionals. The interviews we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…All of the above PS factors fall within the scope of HL. Based on these facts, our research hypotheses state that HL impacts both PS and QC (Figure 1 The hypotheses of the model in Figure 1 were supported and consolidated in an exploratory qualitative study in the form of semi-structured interviews with healthcare professionals and patients in the Moroccan context (Frichi, Jawab & Boutahari, 2019a). The objective of the present study is to confirm empirically the hypothetical model with quantitative data.…”
Section: Hospital Logistics and Its Interaction With Qc And Psmentioning
confidence: 69%
“…All of the above PS factors fall within the scope of HL. Based on these facts, our research hypotheses state that HL impacts both PS and QC (Figure 1 The hypotheses of the model in Figure 1 were supported and consolidated in an exploratory qualitative study in the form of semi-structured interviews with healthcare professionals and patients in the Moroccan context (Frichi, Jawab & Boutahari, 2019a). The objective of the present study is to confirm empirically the hypothetical model with quantitative data.…”
Section: Hospital Logistics and Its Interaction With Qc And Psmentioning
confidence: 69%
“…Data collection processes used the following sources: semi-structured interviews, consultation of internal RENAUTLT's documents, and observations. Semi-structured interviews allow collecting data by interviewing participants using an interview guide [48], which contains all covered topics ( Table 3). The interview guide was elaborated based on the literature review, which identified motivators, barriers, benefits, and prerequisites for implementing synchronous flow.…”
Section: Data Collection Processmentioning
confidence: 99%